MODERN INFORMATION TECHNOLOGIES IN TOURISM (Development Service Industry Management, 2024)
The relevance of the introduction of modern information technologies in the activities of tourist companies is considered. In today's conditions of fierce competition and market economy, no successful company can fully develop and effectively advance in the market without modern automated information technologies. Informatization in the field of management of the economic activity of a tourist company is carried out with the aim of increasing the productivity of the staff at the expense of reducing the cost of services; as well as improving the qualifications and professional knowledge of specialists.The classification of information technologies is given. At the current stage of the operation of tourism business enterprises, objective factors arise that complicate the processes of making management decisions, in the conditions of an accelerated pace of social and political life. The volume of "professional" information that should be mastered and used in everyday activities is increasing, science and technology are rapidly developing, which encourages the introduction of more productive and qualitatively new technologies, the latest information technologies and the provision of a wide range of services. The main advantages of the introduction of modern information technologies are noted. The information technology system of the hospitality industry is considered. Today, there is a large number of software products aimed at automating the management processes of travel firms. The main tourist portals used by domestic tourism business entities are most often used by the computer reservation system.
Keywords: tourist business; informatization; tourist company; management; information technologies; communication technologies; network technologies; tourist portals